TAWASSUL IN THE QAṢĪDAH YARTĀḤ QALBĪ BY ḤABĪB ‘UMAR IBN ḤAFĪẒ: A SEMIOTIC STUDY OF MICHAEL RIFFATERRE - Isnarti Isnarti; Cahya Buana; Irfan Abubakar; Ahfa Rahman Syah; Minatur Rokhim (CMES (Center of Middle Eastern Studies), 2025)
Ḥabīb ‘Umar Ibn Ḥafīẓ is a renowned preacher from Tarim who has produced numerous literary works, including poetry and qaṣīdahs. One of them, Yartāḥ Qalbī, conveys profound meanings of tawassul expressed through poetic and refined language. This study aims to explore the symbolic meanings and the forms of tawassul within the qaṣīdah. The research employs a descriptive qualitative method using Michael Riffaterre’s semiotic approach, which includes indirect expression, heuristic and hermeneutic reading, matrix, model, variant, hypogram, and intertextuality. The analysis reveals that Yartāḥ Qalbī is rich in rhetorical devices, consisting of eight metaphors, two metonymies, one personification, and one hyperbole, all of which reflect deep symbolic meanings related to tawassul. The main finding highlights the practice of tawassul bi-l-maḥabbah, namely supplicating to Allah by means of love and the honor of ahl al-bayt. The concept of tawassul in this qaṣīdah is not merely ritual but also embodied in forms of praise and supplication. Therefore, Yartāḥ Qalbī not only expresses devotion to ahl al-bayt but also serves as a medium for preserving the tradition of tawassul and reinforcing the spiritual and faith values of the Muslim community.